The burden of childhood injuries and evidence based strategies developed using the injury surveillance system in Pasto, Colombia. (27th January 2011) - Espitia-Hardeman, Victoria; Borse, Nagesh N; Dellinger, Ann M; Betancourt, Carmen Elena; Villareal, Alba Nelly; Caicedo, Luz Diana; Portillo, Carlos
Abstract : Objective: This article characterises the burden of childhood injuries and provides examples of evidence–based injury prevention strategies developed using a citywide injury surveillance system in Pasto, Colombia. Methods: Fatal (2003-2007) and non-fatal (2006-2007) childhood injury data were analysed by age, sex, cause, intent, place of occurrence, and disposition. Results: Boys accounted for 71.5% of fatal and 64.9% of non-fatal injuries. The overall fatality rate for all injuries was 170.8 per 100, 000 and the non-fatal injury rate was 4, 053 per 100, 000. Unintentional injuries were the leading causes of fatal injuries for all age groups, except for those 15-19 years whose top four leading causes were violence-related. Among non-fatal injuries, falls was the leading mechanism in the group 0-14 years. Interpersonal violence with a sharp object was the most important cause for boys aged 15-19 years. Home was the most frequent place of occurrence for both fatal and non-fatal injuries for young children 0-4 years old. Home, school and public places became an important place for injuries for boys in the age group 5-15 years. The highest case-fatality rate was for self-inflicted injuries (8.9%). Conclusions: Although some interventions have been implemented in Pasto to reduce injuries, it is necessary to further explore risk factors to better focus prevention strategies and their evaluation. We discuss three evidence-based strategies developed to prevent firework-related injuries during festival, self-inflicted injuries, and road traffic-related injuries, designed and implemented based on the injury surveillance data.